Treatment of Neglegted Sternoclavicular (SC) Dislocation with Cannulated Screw and Cerclage Wire Osteosynthesis - Azharuddin Azharuddin (Universitas Syiah Kuala, 2014)
Treatment of Neglegted Sternoclavicular (SC) Dislocation with Cannulated Screw and Cerclage Wire Osteosynthesis